THE INFLUENCE OF TIME ON PAYMENT DECISIONS IN THE CONTEXT OF PAY AS YOU WANT IN INDONESIA: BEFORE OR AFTER? - Fitrianti, Nida Garnida; Yolistina , Anggun; Fatmasari, Raden Roro (Journal of Jabar Economic Society Networking Forum, 2024)
Changes in payment patterns, both before and after delivery of goods or services, have become an increasingly important topic in the modern business context, especially in Indonesia. This paper investigates the impact of changes in payment patterns on business efficiency, transaction security, and consumer confidence in Indonesia. Through an analysis of the cultural, technological, and economic factors that influence payment preferences, as well as the role of consumer behavior and business habits in payment decisions, this paper outlines how payment patterns have shifted from payment upon receipt of goods or services toward payment before delivery. The impact of changing payment patterns on business efficiency is reflected in the improvement of a company's cash flow and liquidity with pre-delivery payments, while post-delivery payments can lead to delays in payments and the risk of delayed or unpaid payments. In addition, changes in payment patterns also have significant implications for transaction security, where payment before delivery can increase transaction security by reducing the risk of fraud, but also increases the risk of duplicate payments. Consumer confidence is also influenced by the payment pattern chosen, with payment before delivery providing a guarantee of the quality of the goods or services received, while payment after delivery can provide an opportunity for consumers to check the quality of the goods before paying in full. Therefore, further research is needed to better understand consumer payment preferences, as well as to develop solutions that can overcome challenges and optimize the benefits of different payment patterns. Thus, implementing the right payment pattern can be one of the keys to achieving business success in this digital era, while still prioritizing security, efficiency and consumer trust.